Lung ultrasound: an additional tool in COVID-19 - Oliveira,Rodrigo Ribeiro de (2020)
Abstract Lung ultrasound is a well-defined diagnostic modality in the point of care emergency medicine concept. In the context of the coronavirus disease 2019 (COVID-19) pandemic, the lung ultrasound assumed an essential role in this disease, with a valid correlation of the imaging results with computed tomography. Recognize how the diagnostic possibilities of ultrasound in the approach of COVID-19 and its differential diagnoses are fundamental.